COMPARISON RESULT FOR THE PREDICTION ACCURACY OF SEAWATER INTRUSION BASED ON DIFFERENT SAMPLE SIZES AND LAND COVER CHARACTERISTICS USING INVERSE DISTANCE WEIGHTING AND KRIGING - Suastini, Ni Made Mega Melliana; Ghazali, Mochammad Firman; Dermawan, Ananda; Salsabila, Choirunnisa; Zahra, Lauditta; Aulia, Mila (UI Scholars Hub, 2023)
This study aims to determine seawater intrusion (SWI) based on sample sizes' contribution to land cover characteristics' accuracy using inverse distance weighting (IDW) and Kriging. The SWI is explained based on the extracted salt concentration from the dissolved soil. Here, this study used 24 samples of salt concentration, namely salinity samples collected by systematic random sampling and divided into two groups: ground control points (GCP) and independent checkpoints (ICP). Two interpolation methods, namely IDW and Kriging, are used to make a spatial prediction of the SWI, and their results are evaluated based on their accuracy by observing the root mean square error (RMSE). Based on the results of the best interpolation method using various sample size scenarios considering the knowledge to consider sufficient samples for SWI estimation, namely, the Kriging method produces the lowest RMSE value of 0.011 in model 1 and the highest RMSE value of 0.025 in model 3. The kriging method does not work well if the sample number is small. Compared to IDW, which has the highest RMSE value of 0.028 in model 3 and the lowest RMSE value of 0.13, respectively, in model 1. At the same time, the IDW method can work well even though the sample size is small. However, both interpolation methods are suitable for detecting seawater intrusion in Way Urang Village. In this study also, land cover affects the dynamics of salt concentration so that open land may have a higher salinity value than shrubs and vegetation with low salinity values causing the soil in Way Urang Village not to be polluted by seawater intrusion because the salinity concentration does not exceed the limit.